Chemometric recognition of oil–source in the western the Ordos Basin, China. (March 2023) - Li, Yaoting; Chen, Shijia; Zhang, Haifeng; Feng, Li
Abstract: In recent years, significant breakthroughs in the exploration and development of tight oil in the Lower Triassic Yanchang Formation of the Ordos Basin have been achieved. However, there is still a lack of genetic relationship analysis of oil sources in this basin on a large scale. In this study, we performed Rock–Eval pyrolysis to analyze 41 source rocks in four study areas. A total of 79 crude oil and source rock samples from this region was analyzed using gas chromatography mass spectrometry to identify the geochemical characteristics of crude oil and source rocks. Based on 16 biomarker parameters, we used principal component analysis and multidimensional scaling for the analysis of the crude oil source. Combined with alternating least squares, we quantitatively calculated the contribution rate of source rocks to crude oil. The results indicated that the region can be divided into four types of oil sources: the Habahu area in the northwest of the basin, the Huanxian area in the west of the basin, the Pengyang area in the southwest of the basin, and the center of basin. The oil–source comparison results reveal that the reservoirs in the central basin are of single crude oil, whereas those in the Habahu, Huanxian, and Pengyang areas are mixed crude oil. Based on ALS, the relative contribution rates of source rocks in each area to different samples were determined. The present research provides us with a valuable method to use a variety of chemometrics methods to jointly judge the crude oil source and the classification of gene groups. Highlights: The traditional oil source correlation research method of Yanchang Formation in the southwest of Ordos Basin is insufficient. Comprehensive analysis of crude oil source by various chemometrics methods. Quantitative calculation of contribution rate of source rocks to crude oil by Alternating Least Squares (ALS).